A Comparative Study of the Effectiveness of Short-Term Psychodynamic Psychotherapy and Acceptance and Commitment Therapy on Communication Patterns in Women Involved in Extramarital Relationships - Jafari, Masoome; Gohari, Behzad Ali; Davari, Rahim (Psychology of Woman Journal, 2027)
Objective: The present study aimed to compare the effectiveness of Short-Term Psychodynamic Psychotherapy (STPP) and Acceptance and Commitment Therapy (ACT) on communication patterns among women involved in extramarital relationships.Methods and Materials: This quasi-experimental study employed a three-group design with pretest, posttest, and two-month follow-up assessments. The statistical population consisted of married women with a history of extramarital relationships who attended counseling centers affiliated with the Tehran Welfare Organization and the Iranian Psychological Association in 2026. Forty-five participants were selected through volunteer sampling and randomly assigned to three groups: STPP (n = 15), ACT (n = 15), and a control group (n = 15). The intervention groups received eight weekly individual therapy sessions, while the control group received no structured intervention. Data were collected using the Communication Patterns Questionnaire (CPQ) and analyzed using descriptive statistics, Kruskal–Wallis tests, repeated-measures ANCOVA, Welch tests, and Bonferroni post hoc comparisons in SPSS-27.Findings: No significant differences were observed among the groups at baseline for mutual constructive communication, demand–withdraw communication, or mutual avoidance communication (p > .05). Repeated-measures ANCOVA demonstrated significant Time × Group interactions for mutual constructive communication (F = 4.379, p = .020, η² = .196) and demand–withdraw communication (F = 12.842, p < .001, η² = .416), indicating superior improvement in the intervention groups compared with the control group. Significant between-group effects were also observed for mutual constructive communication (F = 20.373, p < .001, η² = .531), demand–withdraw communication (F = 136.480, p < .001, η² = .883), and mutual avoidance communication (F = 101.130, p < .001, η² = .849). Bonferroni analyses revealed that STPP produced significantly greater improvements at follow-up in constructive communication and reductions in demand–withdraw patterns, whereas ACT showed the lowest levels of mutual avoidance communication.Conclusion: Both STPP and ACT were effective interventions for improving communication patterns among women involved in extramarital relationships. However, STPP demonstrated stronger and more durable effects on enhancing constructive communication and reducing demand–withdraw interactions, while ACT was particularly effective in reducing communication avoidance. These findings support the clinical utility of both approaches for addressing communication difficulties and promoting healthier marital interactions in women experiencing relational distress associated with extramarital involvement.